New Situations-New Demands in Our Educational System – Learning Foreign Languages - Kh.Yu. Olimov; D.S.Jalolova (International Journal on Orange Technologies, 2021)
The article examines the development of educational and informational competences of students in the Pedagogics reform and the formation of professional qualities of future educators